PENGARUH KUALITAS PRODUK DAN LOKASI TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA KONSUMEN KARUNIA KASIH ABADI FURNITURE) - Vonita Anggun Dewi Kumala; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT The high competition in the business world specifically in the world of Furniture business, business people are required to provide satisfaction to consumers. After consumers are satisfied, they will get a positive level of loyalty. Customers will no doubt return and make profitable repeat and automatic purchases for entrepreneurs. For this reason, it is necessary to think about what factors influence customer satisfaction so that entrepreneurs can meet customer satisfaction. This study aimed to determine the differences in Product Quality, Location and Satisfaction with Customer Loyalty in the Karunia kasih Abadi Furniture. The population is consumers of the Karunia Kasih Abadi Furniture. The sample used was 86 people. Data collection is done by collecting questionnaires with purposive sampling techniques. The data analysis used path analysis. Where Product Quality as X1, Location X2, Y Satisfaction and Z Loyalty. The results in this study showed a positive and significant relationship between Product Quality and Location to Purchasing Loyalty through Satisfaction as an Intervening variable. Keywords : Product Quality, Location, Customer Loyalty and Satisfaction